Hauptzentrum Köln-Chorweiler. - (:unkn) unknown (My University, 1976)
Die Broschüre informiert über die Entstehung der Neuen Stadt Köln-Chorweiler.
Keywords: Städtebau; Stadtviertel; Stadtplanung; Satellitenstadt; Trabantenstadt; Stadtplanung; Stadtentwicklungsplanung